KEPEMIMPINAN PENGAWAS, KEPALA SEKOLAH, DAN GURU DALAM PENINGKATAN TARGET KURIKULUM - Nia Wardhani (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan, 2018)
School management is one of the factors that affect the education quality. This is because school management will influence and define the effectiveness of the curriculum, numerous learning tools, teaching time and the learning process. School management is the process of employing all school resources run through rational and systematic act (comprising; planning, organizing, actions and controlling) in order to reach school goals effectively and efficiently. Effective schools are under schools management which have characteristics: Supervisors, principals and teachers who have high attention to increase the quality of teaching, teachers who have high expectations to support student achievement, the climate of the school which is not firm, cool without pressure and conducive in the whole teaching process, the school has a wide understanding of the focus of teaching and struggles for the effectiveness of the school by using all school resources to achieve the goals completely, effective schools can guarantee the progress of students that are monitored periodically.